The attractiveness of foreign direct investment in Russia and Ukraine: A statistical analysis - Olga Nosova (Universität Potsdam, Wirtschafts- und Sozialwissenschaftliche Fakultät, 1999)
In this paper a comparative exploration of the potential for foreign investment and real inflow to Russia and Ukraine are examined. The analysis showed that primarily both countries enjoyed significant comparative advantages in attracting foreign capital. Since the foundation of independent states in 1992 attractiveness began to diverge dramatically. This difference is clearly explained by the determination of the Russian government to reform the economy earlier than the Ukrainian government. The transition to a market economy is closely connected with the development of a favorable investment climate in both countries. It includes the foundation of a stable system of property rights and a conducive legal environment.
urn:nbn:de:kobv:517-opus-12079
Keywords: 330; foreign direct investment; investment climate; system of property rights